The life-cycle energy and environmental emissions of a typical offshore wind farm in China. (10th April 2018) - Yang, Juhua; Chang, Yuan; Zhang, Lixiao; Hao, Yan; Yan, Qin; Wang, Changbo
Abstract: China's vast untapped offshore wind energy and the concentration of electricity consumers in coastal regions make offshore wind power a promising solution to the country's cleaner power transition. However, the potential energy and environmental emissions of offshore wind farms have not been thoroughly investigated. Thus, this study employed a process-based life cycle inventory (LCI) model to calculate the life-cycle energy and emissions of offshore wind power in China based on the country's first offshore wind energy project. Results showed that the life-cycle energy of the studied wind farm was 2.28E+09 MJ, or 0.39 MJ/kwh, with emission intensities of 25.5 g CO2 -eq/kWh for GHG, 0.02 g/kWh for PM2.5, 0.06 g/kWh for SO2 and 0.09 g/kWh for NOx . The life-cycle footprints are dominated by the manufacture of wind turbines and foundation materials production. Compared to onshore wind farms, offshore wind power plants usually have greater life-cycle electricity yields, but their levelized energy and environmental footprints are less favorable. The green manufacturing of China's steel sector, and scientific operation and maintenance programs of wind facilities contribute to greening offshore wind power. Results of this study facilitate robust policy making of government authorities and contribute to the green deployment of offshore wind technologies in China. Highlights: A process-based LCI was conducted for the first offshore wind power plant in China. The life-cycle energy, GHG, SO2, NOx, and PM2.5 emissions were calculated. The life-cycle footprints are dominated by wind turbines manufacture and foundation materials production. The environmental performance of offshore wind farms is inferior to that of onshore wind farms.